A novel filamentous cyanobacterium Microseira minor sp. nov. (Oscillatoriaceae, Cyanobacteria) from the Ganfu Channel, Jiangxi, China - Geng, Ruozhen; Wen, Qianzhi; Wang, Yilang; Yang, Ping; Dai, Guofei; Li, Renhui; Yu, Gongliang (Phytotaxa, 2021)
Two filamentous cyanobacterial strains were isolated from the mats attached to rock surfaces in the Ganfu Channel, Jiangxi Province, China. A polyphasic approach based on the combination of morphological and molecular features was used to characterize the two strains. Both strains showed the Lyngbya-like morphology under the light microscopy, and had the highest similarity range of 16S rRNA gene sequences as 95.00-96.01% to clones of Microseira wollei, exceeding the cutoff for species delimitation in cyanobacteria. Phylogenetic analyses based on both 16S rRNA and nifH genes and smaller sizes of trichomes in the two Lyngbya-like strains supported them to be proposed as a new species in the genus Microseira as Microseira minor, which is the second species of the genus Microseira. The difference of the 16S-23S ITS region between the two Microseira minor strains and its implication for the evaluation on cyanobacterial diversity and species differentiation were also discussed.